Zooplankton of Chaun Bay (East-Siberian Sea), Russia, 1986 - Alexi Pinchuk (Arctic Data Center, 2014)
This dataset represents zooplankton data collected from Chaun Bay, Russia, 1986. Characteristics of distribution and seasonal variations in the composition and members of the dominant zooplankton typical of the Chaun Bay are shown.Only predominant species are included for both abundance and biomass estimates. Thus null values may not be zero but rather not recorded as taxa is not dominant. Samples were collected with a Juday net of 163 um mesh size and mouth opening diameter of 0.75 meters. The samples were fixed in a 4% formalin solution.